Subtle Changes in Surface-tethered Groups on PEGylated DNA Nanoparticles Significantly Influence Gene Transfection and Cellular Uptake - Ke, Xiyu (Nanomedicine, 2019)
PEGylation strategy has been widely used to enhance colloidal stability of polycation/DNA nanoparticles (NPs) for gene delivery. To investigate the effect of polyethylene glycol (PEG) terminal groups on the transfection properties of these NPs, we synthesized DNA NPs using PEG-g-linear polyethyleneimine (lPEI) with PEG terminal groups containing alkyl chains of various length with or without a hydroxyl terminal group. For both alkyl- and hydroxyalkyl-decorated NPs with PEG grafting densities of 1.5, 3, or 5% on lPEI, the highest levels of transfection and uptake were consistently achieved at intermediate alkyl chain lengths of 3 to 6 carbons, where the transfection efficiency is significantly higher than that of nonfunctionalized lPEI/DNA NPs. Molecular dynamics simulations revealed that both alkyl- and hydroxyalkyl-decorated NPs with intermediate alkyl chain length exhibited more rapid engulfment than NPs with shorter or longer alkyl chains. This study identifies a new parameter for the engineering design of PEGylated DNA NPs.